Pengaruh Tax Avoidance, Kebijakan Hutang, Dan Profitabilitas Terhadap Nilai Perusahaan Pada Perusahaan LQ 45 Yang Terdaftar Di Bursa Efek Indonesia Periode 2016 – 2021 - Erika Diah Safitri; Jeni Susyanti; Mohamad Bastomi (UNIVERSITAS ISLAM MALANG, 2023)
Abstract Low stock prices can result in a decrease in the value of the company in the eyes of investors due to several factors. The purpose of this study was to determine the effect of tax avoidance, debt policy, and profitability on firm value with dividend policy as moderating variable for LQ45 companies. The research is a quantitative research using secondary data. The population in this research is LQ45 companies for the period 2016 – 2021. The technique of taking samples using purposive sampling method. In this study 17 samples of LQ45 companies with a total sample data of 102 samples. This study uses multiple regression analysis and Moderated Regression Analysis (MRA) using SPSS 16. The results of this study indicate that (1) tax avoidance has no effect of firm value, (2) debt policy has a positive and significant effect on firm value, (3) profitability has a positive and significant effect on firm value. Keywords: Tax Avoidance, Debt Policy, Profitability, Firm Value